La educación virtual en la Universidad Central del Ecuador: ¿un nuevo reto académico? (Estudios) - Morillo Revelo, Javier (2022)
This research addresses the management of educational knowledge using information and communication technologies (ICT) tools at Universidad Central del Ecuador (UCE), specifically at the Faculty of Administrative Sciences, to analyze how technological scientific progress influences higher education in the context of the COVID-19 pandemic. The objective is to analyze the use of new competencies backed by virtual educational platforms, in order to improve the teaching - learning process and the autonomous capacity of students. This study is descriptive in nature due to the theoretical perspective of the subject in terms of the management of knowledge in the educational field; on the other hand, the use of the quantitative typology is due to the operability of statistical figures and the use of the scientific method, with a technical application of a field study by means of surveys. The conclusion is that the use of ICTs in knowledge management is currently the support engine in the teaching-learning process, promoting the growth of teachers through e-learning, and thereby allowing them to fully exploit the capacities of students under equal opportunities.